Bacterial Epimerization as a Route for Deoxynivalenol Detoxification: the Influence of Growth and Environmental Conditions - He, Jian Wei; Hassan, Yousef I.; Perilla, Norma; Li, Xiu-Zhen; Boland, Greg J.; Zhou, Ting (Frontiers in Microbiology, 2016)
Deoxynivalenol (DON) is a toxic secondary metabolite produced by several Fusarium species that infest wheat and corn. Food and feed contaminated with DON pose a health risk to both humans and livestock and form a major barrier for international trade. Microbial detoxification represents an alternative approach to the physical and chemical detoxification methods of DON-contaminated grains. The present study details the characterization of a novel bacterium, Devosia mutans 17-2-E-8, that is capable of transforming DON to a non-toxic stereoisomer, 3-epi-deoxynivalenol under aerobic conditions, mild temperature (25-30 oC), and neutral pH. The biotransformation takes place in the presence of rich sources of organic nitrogen and carbon without the need of DON to be the sole carbon source. The process is enzymatic in nature and endures a high detoxification capacity (3 µg DON/h/108 cells). The above conditions collectively suggest the possibility of utilizing the isolated bacterium as a feed treatment to address DON contamination under empirical field conditions.